2022
DOI: 10.3934/jimo.2021138
|View full text |Cite
|
Sign up to set email alerts
|

Asset allocation for a DC pension plan with learning about stock return predictability

Abstract: <p style='text-indent:20px;'>This paper investigates an optimal investment problem for a defined contribution pension plan member who receives a stochastic salary, and considers inflation risk and stock return predictability. The member aims to maximize the expected power utility from her terminal real wealth by investing her pension account wealth in a financial market consisting of a risk-free asset, an inflation-indexed bond and a stock. The expected excess return on the stock can be predicted by both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The results showed that partial information could affect the investment proportion of stocks. Applying filtering technology and the stochastic dynamic programming method, Wang et al (2022) [37] derived the optimal investment strategy for a DC pension plan with stock return predictability and inflation risk. The study highlighted that the predictability of the partially observable stock returns yield plays a crucial role in the optimal investment strategy for inflation-indexed bonds.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that partial information could affect the investment proportion of stocks. Applying filtering technology and the stochastic dynamic programming method, Wang et al (2022) [37] derived the optimal investment strategy for a DC pension plan with stock return predictability and inflation risk. The study highlighted that the predictability of the partially observable stock returns yield plays a crucial role in the optimal investment strategy for inflation-indexed bonds.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al [23] derived the optimal investment strategy for DC pension fund with the mean-variance criterion under partial information. For more literature on optimal asset allocation strategies for DC pension funds, please refer to Bian et al [3], Chang et al [5], Gerrard et al [11], Li et al [22], Wang et al [28], Wang et al [29], Wu et al [32], Yao et al [35], Zhang et al [37], Zhao et al [39] and many others.…”
mentioning
confidence: 99%
“…The TBP differs from the traditional defined contribution (DC) pension plan and defined benefit (DB) pension plan. Relevant literature on DC is mainly concerned with optimal investment strategies, which can refer to Gerrard [10], He and Liang [14], [13], Vigna [25],Zhao et al [35],Zeng et al [34], Chang et al [4], Wang et al [28], Yao et al [33] and much others. Most of the existing studies on the DB plan focus on optimal investment strategies and contribution policies to minimize the solvency risk and contribution risk, which can see Haberman et al [11], Josa-Fombellida and Rincón-Zapatero [16], [17], [18] and much others.…”
mentioning
confidence: 99%